The contested city: Speculative fiction and metropolitan imagination in colonial Bengal. Issue 6 (2nd November 2022) - Bhattacharya, Atanu; Hiradhar, Preet
ABSTRACT: Speculative fiction emerged in 19th-century Bengal as a mode of narrative engagement with the city's colonial modernity during its contact with British colonialism. This fiction, however, was essentially a city-based enterprise interacting with, and moulding, the imperial city of Kolkata in myriad ways. The interaction gave rise to dissenting voices within the gradually emerging educated class of Kolkata. This article explores such intersections of the city and speculative fiction with the aid of two conceptual arcs – morality and corporeality – and argues that, located within divergent imaginaries of representing the city, they construct a contested cityscape. These arcs produce an alternative metropolitan imagination that subverts the colonial imaginary of the city. The article examines two early speculative texts written by Kylas Chunder Dutt and Shoshee Chunder Dutt to explore the nature of this imagination. The colonial imaginary of Kolkata within this speculative textual space offers a locus distinct from the colonizers.